Liquid heavy metal reactor aerosol protective coating and preparation method thereof

Through the double-layer coating structure, combined with the design of polymer and hydrogel, the problem of capturing heavy metal radioactive aerosols is solved, and efficient aerosol capture and stability improvement are achieved, which is suitable for the protection of nuclear power plants.

CN120590829APending Publication Date: 2025-09-05CHINA NUCLEAR POWER TECH RES INST CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510881756.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-27
Publication Date
2025-09-05

AI Technical Summary

Technical Problem

Existing coatings are unable to effectively capture heavy metal radioactive aerosols, especially under high irradiation conditions, and there is insufficient research on the inhibition of aerosol resuspension after film formation, making it difficult to control radioactive aerosol pollution in nuclear power plants.

Method used

It adopts a double-layer coating structure, including a polymer coating and a hydrogel coating. The polymer coating provides mechanical properties and peelability, the hydrogel coating imparts viscosity and charge adsorption capabilities, the nano-silver oxide particles enhance the binding ability, and the positively charged ionic liquid improves the electrostatic adsorption effect.

Benefits of technology

It significantly improves the capture effect of heavy metal aerosols, enhances the stability of the coating and the ability to capture re-deposited aerosols, has high tensile strength, excellent elongation at break, high thermal decomposition temperature and strong UV resistance, and is suitable for high radiation environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005472549990000071
    Figure BDA0005472549990000071
  • Figure HDA0005472550000000011
    Figure HDA0005472550000000011
  • Figure HDA0005472550000000012
    Figure HDA0005472550000000012
Patent Text Reader

Abstract

The invention discloses a liquid heavy metal reactor aerosol protective coating and a preparation method and application thereof, and the liquid heavy metal reactor aerosol protective coating comprises a polymer coating prepared from an acrylic monomer, an emulsifier, an initiator and an organic solvent; the hydrogel coating is prepared from acrylamide, acrylic acid, a cross-linking agent, a photoinitiator and ionic liquid with positive charges; the polymer coating and the hydrogel coating are loaded with nano silver oxide particles. The double-layer coating disclosed by the invention has a relatively good capturing effect on resettled aerosol in air after film formation. A solvent is fixed in the upper hydrogel coating, the solvent is released at a gel-aerosol interface, the surface is locally wetted, and the effects of covering, wetting, adhering, adsorbing and the like on resettled aerosol particles are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of material technology, in particular to a liquid heavy metal reactor aerosol protective coating and a preparation method thereof. Background Art

[0002] Currently, global nuclear power technology has largely completed its transition to third-generation nuclear power and is entering the fourth-generation technology R&D phase, along with engineering demonstrations and verification of selected reactor types. While fourth-generation reactors are developing rapidly, they are still some distance away from practical production deployment. For example, fourth-generation reactors inevitably generate radioactive heavy metal aerosols. These fission products, present in the coolant and blanket gas within the reactor circuits, are highly toxic and volatile, posing a significant risk to operators and the public. Due to the inherent leakage rate of blanket gas, circuit openings, filter replacements, and personnel handling during decommissioning or maintenance can all lead to the escape of gases containing heavy metal radionuclides, resulting in air pollution from radioactive heavy metal aerosols within nuclear power plants.

[0003] At present, great progress has been made in the study of the morphology of heavy metal radioactive aerosols, but there are still great limitations in the capture of heavy metal radioactive aerosols; the capture of heavy metal radioactive aerosols in power plants is mainly aimed at nuclear accidents, and there is less discussion on the decommissioning and decontamination of nuclear facilities; previous studies have mainly focused on the suppression of aerosols, and there has been no research on the resuspension of aerosols after film formation; the influencing factors of aerosol resuspension inhibition (such as the charge, adhesion, wettability, etc. of the coating) need to be studied in detail, and the capture mechanism of aerosols by the coating under high irradiation conditions is still unclear.

[0004] Peelable coatings are a widely used decontamination method that can effectively remove loose aerosols from surfaces. Currently, waste pits, walls, floors, and personal protective equipment such as seat belts all use sprayed or brushed coatings to remove the corresponding loose pollution. However, existing coatings cannot have a fixed effect on the secondary suspension of aerosols. Summary of the Invention

[0005] The present invention aims to solve at least one of the above-mentioned technical problems in the prior art. To this end, the present invention aims to provide a liquid heavy metal reactor aerosol protective coating and a preparation method thereof.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is:

[0007] A first aspect of the present invention provides a liquid heavy metal reactor aerosol protective coating, comprising:

[0008] The polymer coating is prepared from acrylic monomers, emulsifiers, initiators, and organic solvents;

[0009] A hydrogel coating is prepared from acrylamide, acrylic acid, a crosslinking agent, a photoinitiator, and a positively charged ionic liquid;

[0010] The polymer coating and the hydrogel coating are both loaded with nano silver oxide particles.

[0011] In the present invention, a high polymer coating is used as the substrate to ensure the mechanical properties and peelability of the protective coating, while focusing on the capture of settled aerosols; the upper layer is a hydrogel coating, which gives it viscosity and ensures the capture of re-settled aerosols after film formation; the ionic liquid fixed in the hydrogel coating is released at the hydrogel-aerosol interface, locally wetting the surface, which is beneficial to the coverage, wetting, adhesion, and adsorption of re-settled aerosol particles; different from conventional peelable films formed by covalent cross-linking, which usually produce static networks that cannot be reformed after rupture, the polymer network in the hydrogel coating of the present invention has the property of swelling without dissolving when the solvent quality, gel network or environment changes, significantly improving the stability of the protective coating; the nano-silver oxide particles in the coating significantly increase the coating's binding ability for heavy metal-containing aerosols, and the positively charged ionic liquid in the hydrogel coating has an electrostatic adsorption effect on heavy metal-containing aerosols.

[0012] In some embodiments of the present invention, the thickness ratio of the polymer coating to the hydrogel coating is 1:(0.5-1.5).

[0013] In some embodiments of the present invention, the thickness of the liquid heavy metal reactor aerosol protective coating is 0.1 to 20 mm.

[0014] In some embodiments of the present invention, in the polymer coating, the mass ratio of acrylic monomer, emulsifier, initiator, and organic solvent is (1-10):(1-5):(10-50).

[0015] In some embodiments of the present invention, in the hydrogel coating, the mass ratio of acrylamide, acrylic acid, crosslinker, photoinitiator, and positively charged ionic liquid is (0.5-5):(0.1-1):(0.001-0.01)(0.001-0.01):(0.1-0.5).

[0016] In some embodiments of the present invention, the mass percentage of the nano silver oxide particles in the polymer coating is 0.1 wt% to 5 wt%.

[0017] In some embodiments of the present invention, the average particle size of the nano silver oxide particles is 50 to 100 nm.

[0018] In some embodiments of the present invention, the acrylic acid-based monomer includes at least three of methyl methacrylate, isobornyl methacrylate, ethyl methacrylate, butyl methacrylate, butyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate and acrylic acid; when there are three, they include butyl acrylate, methyl methacrylate, and acrylic acid, and the mass ratio of the three is (0.5-2):(0.8-2):0.1; when there are four, they include butyl acrylate, methyl methacrylate, ethyl methacrylate, and acrylic acid, and the mass ratio of the four is (0.5-2):(0.4-1):(0.4-1):0.1.

[0019] In some embodiments of the present invention, the emulsifier includes a nonionic emulsifier and an anionic emulsifier; the anionic emulsifier includes at least one of sodium lauryl sulfate, sodium dodecylbenzenesulfonate, and ammonium sulfate of alkylphenol ethoxylate. The nonionic emulsifier includes at least one of octylphenol polyoxyethylene ether and alkylphenol polyoxyethylene ether.

[0020] In some embodiments of the present invention, the initiator includes at least one of ammonium persulfate, potassium persulfate, and tert-butyl hydroperoxide.

[0021] In some embodiments of the present invention, the organic solvent includes an alcohol ether organic solvent and / or an alcohol ester organic solvent; the alcohol ether organic solvent includes at least one of propylene glycol butyl ether, ethylene glycol butyl ether, and dipropylene glycol monoether; and the alcohol ester includes at least one of dodecyl alcohol ester.

[0022] In some embodiments of the present invention, the cross-linking agent includes at least one of N,N'-methylene acrylamide (MBA), N,N'-methylenebisacrylamide (BIS), epichlorohydrin (ECH), dicumyl peroxide (DCP), benzoyl peroxide (BPO), di-tert-butyl peroxide (DTBP), diisopropyl peroxide (DBCP), propylbenzene divinylbenzene, and diisocyanate.

[0023] In some embodiments of the present invention, the photoinitiator includes at least one of photoresponse agent 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone), 2-hydroxy-2-methyl-1-phenylmethanone, 1-hydroxy-cyclohexyl-phenylmethanone, 2,4,6-trimethylbenzoyl-diphenylphosphine oxide, and 2,2'-azobisisobutylamidine dihydrochloride.

[0024] In some embodiments of the present invention, the positively charged ionic liquid includes at least one of methyltributylphosphine dimethyl phosphate, ethyltributylphosphine tetrafluoroborate, and butyltriphenylphosphine tetrafluoroborate.

[0025] In some embodiments of the present invention, the hydrogel coating further comprises a cross-linking aid; the cross-linking aid comprises at least one of ethylene glycol dimethacrylate (EGDMA), diethylene glycol dimethacrylate, tetraethylene glycol dimethacrylate (TEGDMA), trimethylolpropane trimethacrylate (TMPTMA), glycerol methacrylate, 1,3-propylene glycol dimethacrylate, 2,3-propylene glycol dimethacrylate, 1,6-hexanediol dimethacrylate, and 1,4-butanediol dimethacrylate.

[0026] In some embodiments of the present invention, the hydrogel coating further comprises an acid and / or a base; the acid and / or the base make the pH of the hydrogel solution be 4-6.

[0027] The second aspect of the present invention provides a method for preparing the liquid heavy metal reactor aerosol protective coating, comprising the following steps:

[0028] The acrylic acid monomer is polymerized in the presence of an emulsifier, an initiator, and an organic solvent, and then nano silver oxide particles are added to prepare a polymer coating precursor solution;

[0029] Dissolving acrylamide, acrylic acid, a crosslinking agent, a photoinitiator, and a positively charged ionic liquid, and then adding nano silver oxide particles to prepare a hydrogel coating precursor solution;

[0030] The polymer coating precursor solution is coated to form a film, and then the hydrogel coating precursor solution is coated and photocured to form a film to obtain the liquid heavy metal reactor aerosol protective coating.

[0031] In some embodiments of the present invention, the polymerization reaction is carried out at 70 to 90° C.; and the polymerization reaction time is 2 to 8 hours.

[0032] In some embodiments of the present invention, the photocuring is carried out under ultraviolet light; the wavelength of the ultraviolet light is 275 to 310 nm; the power of the ultraviolet light is 45 to 65 W / cm 2 ; The light curing time is 3 to 10 minutes.

[0033] The third aspect of the present invention provides a use of the liquid heavy metal reactor aerosol protective coating in heavy metal aerosol protection.

[0034] In some embodiments of the present invention, the heavy metal includes at least one of Po, Te, Pb, and Bi.

[0035] The beneficial effects of the present invention are:

[0036] Conventional release films lack the ability to capture re-settled aerosol particles after film formation, while the dual-layer coating of the present invention effectively captures re-settled aerosol particles after film formation. The solvent immobilized in the upper hydrogel coating is released at the gel-aerosol interface, locally wetting the surface and facilitating the coating, wetting, adhesion, and adsorption of re-settled aerosol particles.

[0037] Conventional peelable films are formed through covalent crosslinking, often resulting in a static network that cannot reform if ruptured. However, the hydrogel polymer network in the upper layer of the liquid heavy metal reactor aerosol protective coating of the present invention can swell without dissolving when the solvent quality, gel network, or environment change, thereby improving the stability of the composite.

[0038] Conventional stripping films capture aerosol particles through physical effects such as wetting and coating. The liquid heavy metal reactor aerosol protective coating of the present invention not only ensures the physical effect of the coating on the aerosol, but also increases the chemical adsorption effect of the carried nano-AgO particles on the Po-containing heavy metal aerosol.

[0039] In the liquid heavy metal reactor aerosol protective coating of the present invention, the upper hydrogel coating uses a positively charged ionic liquid solution as a fixed solvent in the hydrogel, so it has an electrostatic adsorption effect on the negatively charged Po-containing aerosol.

[0040] The liquid heavy metal reactor aerosol protective coating of the present invention has high tensile strength, excellent elongation at break, relatively high thermal decomposition temperature, and strong UV resistance. After being irradiated with UV for 50 hours, the coating does not bubble, peel, or crack, and its discoloration and gloss loss are no more than level 1, and its powdering degree is no more than level 1. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 Schematic diagram of the structure of the liquid heavy metal reactor aerosol protective coating and a peeling test diagram of the present invention.

[0042] Figure 2 Schematic diagram of the viscosity of the upper hydrogel coating of the liquid heavy metal reactor aerosol protective coating of the present invention.

[0043] Figure 3 This is a schematic diagram of aerosol attraction by the upper hydrogel coating of the liquid heavy metal reactor aerosol protective coating of the present invention.

[0044] Figure 4 These are the tensile strength and elongation of the liquid heavy metal reactor aerosol protective coating of Example 1 of the present invention.

[0045] Figure 5 These are the tensile strength and elongation of the liquid heavy metal reactor aerosol protective coating of Example 1 of the present invention.

[0046] Figure 6 This is the test process of the xenon lamp aging test of the liquid heavy metal reactor aerosol protective coating of the present invention.

[0047] Figure 7 This is the thermogravimetric analysis result of the liquid heavy metal reactor aerosol protective coating hydrogel coating in Example 1 of the present invention.

[0048] Figure 8 This is the thermogravimetric analysis result of the polymer coating of the liquid heavy metal reactor aerosol protective coating in Example 1 of the present invention. DETAILED DESCRIPTION

[0049] The present invention is further described in detail below using specific examples. Unless otherwise specified, the raw materials, reagents, and apparatus used in the examples and comparative examples are available from conventional commercial sources or by conventional methods. Unless otherwise specified, all experimental or testing methods are conventional in the art.

[0050] In the following examples, the preparation method of nano silver oxide particles is as follows:

[0051] Weigh 0.03g of AgNO3, 0.1000g of citric acid, and 0.04g of NaBH4 in sequence and dissolve them in 100mL, 10mL, and 2mL of distilled water, respectively. Heat and stir the AgNO3 solution until boiling, then slowly add the prepared citric acid solution and NaBH4 solution to it in sequence. After the solution is added dropwise, keep it warm for 30 minutes and then cool it naturally to room temperature. Place the black product in a 100mL centrifuge tube and centrifuge at 9000r / min for 5 minutes. Wash it alternately with water and ethanol three times each, and place it in a vacuum drying oven at 60℃ for 6 hours to obtain black nanosilver particles with a particle size of approximately 50 to 100nm.

[0052] In the following examples or comparative examples, the test standard for tensile strength and elongation at break is GB / T 528-2009.

[0053] The aging resistance test method is as follows:

[0054] Test standard: GB / T 1865-2009

[0055] Irradiation intensity: 60W / m 2 ;

[0056] Temperature: 38±3℃

[0057] Humidity: 40-60% RH;

[0058] Irradiation mode: continuous illumination;

[0059] Test time: 50h.

[0060] Example 1

[0061] This example prepares a liquid heavy metal reactor aerosol protective coating, and the specific process is as follows:

[0062] Preparation of the base polymer coating: Weigh 0.2g of the emulsifier alkylphenol polyoxyethylene ether and 0.2g of sodium lauryl sulfate into 10mL of distilled water, heat and stir at 30°C until dissolved. After cooling to room temperature, add 9mL of distilled water. Add 10mL of the emulsifier solution to a three-necked flask, heat under reflux at 35°C, and mechanically stir at 480 rpm. Weigh 0.24g of ammonium persulfate into 20mL of distilled water and stir until dissolved. To the remaining approximately 10mL of the emulsifier solution, add 3.0g of butyl acrylate, 3.3g of methyl methacrylate, and 0.3g of acrylic acid (butyl acrylate:methyl methacrylate:acrylic acid = 1:1.1:0.1). Pipette 10mL of the ammonium persulfate solution into the monomer solution. Pre-emulsify the monomer solution at 8000 rpm for 5 minutes. Add 10mL of the monomer solution to a three-necked flask and heat with stirring until the emulsion turns from white to blue. Raise the temperature to 75°C, adjust the mechanical stirring rate to 260 rpm, and slowly add the remaining monomer solution to the three-necked flask via a dropping funnel. Control the titration rate to complete the addition over 2 hours. Simultaneously, add 2.5mL of ammonium persulfate solution every 30 minutes. After the addition is complete, raise the temperature to 80°C and add 3mL of dipropylene glycol butyl ether. Maintain the temperature for 2 hours and allow the mixture to cool naturally to room temperature to obtain a base coating precursor solution.

[0063] Preparation of the upper hydrogel coating precursor solution: 3 g of methyl tributylphosphine dimethyl phosphate, 2 g of acrylamide, 0.3 g of acrylic acid, 0.2 g of N,N-methylenebisacrylamide, 0.2 g of photoresponse agent 2959, and 0.3 g of diethanol dimethacrylate were weighed into a beaker respectively, and the mixture was ultrasonically added until the solids were completely dissolved to obtain the upper coating precursor solution.

[0064] 1 wt% nano silver oxide particles were added to the precursor solution to make the mass ratio of the precursor solution 0.1%, and stirred to disperse. 5 mL of the base coating precursor solution was applied to the substrate and allowed to air dry to form a film. After the base coating film was formed, 5 mL of the upper coating precursor solution was applied on it and the wavelength was 275 nm and the power was 60 W / cm 2 The film was solidified by irradiation with ultraviolet light for 5 minutes to obtain a double-layer coating with a thickness of 0.6 mm.

[0065] Schematic diagram of the double-layer coating structure Figure 1 As shown. The liquid heavy metal reactor aerosol protective coating is a composite coating, and the upper hydrogel coating provides adhesion ( Figure 2), responsible for adhering to the heavy metal aerosols that settle after film formation; the lower polymer coating ensures mechanical strength and at the same time plays a role in covering and suppressing the aerosols that have settled on the surface of the substrate. The upper coating has two adsorption modes for the unsettled aerosols: chemical adsorption and charge adsorption. Figure 3 Schematic diagram of charge adsorption of the upper coating.

[0066] After testing, such as Figure 4 、 Figure 5 As shown, the liquid heavy metal reactor aerosol protective coating has a tensile strength of 5.5 MPa and an elongation of 500%, and the coating has high mechanical properties.

[0067] like Figure 6 As shown in the figure, the xenon lamp aging test was carried out. The double-layer coating UV aging test results showed that the double-layer coating had a good thermal stability under the conditions of humidity 40% to 60%, temperature 38±3℃, and irradiation intensity 60W / m 2 After irradiation in a xenon lamp aging test chamber for 50 hours, the coating showed no blistering, peeling, or cracking, and the degree of discoloration and gloss loss was no greater than level 1, and the degree of powdering was no greater than level 1, indicating strong anti-aging ability.

[0068] Figure 7 、 Figure 8 Thermogravimetric testing of the double-layer coating showed that the decomposition temperature of the hydrogel coating was 237°C, ensuring the service life and stability of the coating in high-temperature environments.

[0069] Example 2

[0070] In this example, a liquid heavy metal reactor aerosol protective coating was prepared using the same method as in Example 1, with the difference being that the mass ratio of butyl acrylate, methyl acrylate, and acrylic acid was adjusted to 0.7:1.1:0.1 for butyl acrylate:methyl methacrylate:acrylic acid. Testing showed that the liquid heavy metal reactor aerosol protective coating exhibited an elongation at break of approximately 600% and a tensile strength of approximately 4.9 MPa.

[0071] Example 3

[0072] In this example, a liquid heavy metal reactor aerosol protective coating was prepared using the same method as in Example 1, with the difference being that the mass ratio of butyl acrylate, methyl acrylate, and acrylic acid was adjusted to 1.5:1.1:0.1 for butyl acrylate:methyl methacrylate:acrylic acid. Testing showed that the liquid heavy metal reactor aerosol protective coating exhibited an elongation at break of approximately 800% and a tensile strength of approximately 3 MPa.

[0073] Example 4

[0074] In this example, a liquid heavy metal reactor aerosol protective coating was prepared using the same method as in Example 1, with the difference being that the mass ratio of butyl acrylate, methyl acrylate, and acrylic acid was adjusted to 1:0.9:0.1 for butyl acrylate:methyl methacrylate:acrylic acid. Testing showed that the liquid heavy metal reactor aerosol protective coating exhibited an elongation at break of approximately 800% and a tensile strength of approximately 2.5 MPa.

[0075] Example 5

[0076] In this example, a liquid heavy metal reactor aerosol protective coating was prepared using the same method as in Example 1, except that the mass ratio of butyl acrylate, methyl acrylate, and acrylic acid was adjusted to 1:1.2:0.1. Testing showed that the liquid heavy metal reactor aerosol protective coating exhibited an elongation at break of approximately 600% and a tensile strength of approximately 3.2 MPa.

[0077] Example 6

[0078] In this example, a liquid heavy metal reactor aerosol protective coating was prepared using the same method as in Example 1, except that the mass ratio of butyl acrylate, methyl acrylate, and acrylic acid was adjusted to 1:1.5:0.1. Testing showed that the liquid heavy metal reactor aerosol protective coating exhibited an elongation at break of approximately 400% and a tensile strength of approximately 5.8 MPa.

[0079] Example 7

[0080] In this example, a liquid heavy metal reactor aerosol protective coating was prepared using the same method as in Example 1, except that the mass ratio of acrylic acid to acrylamide was adjusted to 10:1. Testing revealed that the coating exhibited a tensile strength of 5.5 MPa and an elongation of 500%.

[0081] The liquid heavy metal reactor aerosol protective coatings prepared in Example 1 and Example 7 were subjected to aging resistance tests. The results are shown in Table 1:

[0082] Table 1

[0083]

[0084] Example 8

[0085] In this example, a liquid heavy metal reactor aerosol protective coating was prepared. The preparation method was similar to that of Example 1, except that the pH of the upper hydrogel coating precursor solution was adjusted. Specifically, the pH was adjusted to 2-13 using 1 mol / L nitric acid and NaOH solutions, and then the pH was adjusted to 4-6 after shaking.

[0086] The ability of the liquid heavy metal reactor aerosol protective coating to adsorb heavy metal Te was tested. The specific process was as follows: 50 mg of hydrogel was weighed into a 10 mL test tube, 0.4 mL of a prepared 1.7 mg / L sodium tellurite solution was added, and 5 mL of deionized water was added. The pH was adjusted to 2-13 using 1 mol / L nitric acid and NaOH solution, and the pH was adjusted again after shaking until it stabilized. After shaking for 24 hours, the final pH was measured with a pH meter, the solution was filtered through a filter membrane, and the Te concentration was measured using ICP-OES after storage.

[0087] The results showed that when the solution pH was 4-6, it had a strong selectivity for Te and the removal rate could reach up to 96.72%.

[0088] Example 9

[0089] In this embodiment, a liquid heavy metal reactor aerosol protective coating is prepared. The preparation method is similar to that of Example 1, except that the mass proportion of nano-silver oxide particles in the coating is adjusted, specifically, the mass proportion of nano-silver oxide particles is adjusted to 0.5%, 1%, and 2%, respectively.

[0090] After testing, when the content of nano-AgO particles is 2%, the overall tensile strength of the coating is about 1.8MPa, and the elongation at break exceeds 800%; when the content of nano-AgO particles is 1%, the overall tensile strength of the coating is about 4.5MPa, and the elongation at break is about 500%, which will not have a significant negative impact on the mechanical strength of the coating; when the content of nano-AgO particles is 0.5%, the overall tensile strength of the coating is about 2.1MPa, and the elongation at break exceeds 900%. The addition of AgO can significantly affect the ductility of the coating, but will reduce the tensile strength. In addition, Ag + The addition of can effectively enhance the coating's carrying capacity for heavy metal aerosol particles.

[0091] Comparative Example 1

[0092] This comparative example prepares a coating, which differs from Example 1 in that it does not include an upper hydrogel coating.

[0093] A single-layer base coating cannot have adhesion, wetting, adsorption, etc. effects on surface aerosols.

[0094] Comparative Example 2

[0095] This comparative example prepared a coating that differed from Example 1 in that it did not include a base polymer coating.

[0096] After testing, the tensile strength of the coating was 0.8MPa, which could not meet the requirements.

[0097] Test example

[0098] This test example tests the heavy metal capture effect of the coatings prepared in the examples and comparative examples. The specific process is as follows:

[0099] Heavy metal capture effect test of single-layer hydrogel coating: Take 20mL of hydrogel precursor solution, add 0.4mL of prepared 1.7mg / L sodium tellurite solution, and supplement with deionized water. Adjust the pH of the solution to 2-13 with acid and alkali solutions. After shaking for 24h, readjust the pH to a stable state, then filter the solution with a filter membrane, and measure the remaining Te content after preservation treatment.

[0100] The results show that when the pH of the precursor solution is 4-6, the Te removal rate can reach 95%, but the mechanical properties of the coating decrease significantly after absorbing water, and it is easy to break, and cannot meet the protection requirements.

[0101] By analogy between Te and Po, the removal efficiency of Po can be obtained.

[0102] Capture test of heavy metal aerosols of single-layer base coating: Single-layer base coating cannot capture upper layer aerosols and can only perform operations such as adhesion and peeling on settled aerosols.

[0103] Te-carrying dust was evenly applied to different test panels by manual spraying. 20 mL of the base solution was then applied to the panels. The coating was allowed to cure after 12 hours and then peeled off. The element content on the panel surface was measured after peeling to calculate the removal efficiency of the base coating on settled loose contaminants.

[0104] The results show that when the ratio of butyl acrylate:methyl methacrylate:acrylic acid is 1:1.1:0.1, the coating has a high removal efficiency for loose aerosols, which can reach 90%.

[0105] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be considered as equivalent replacement methods and are included in the scope of protection of the present invention.

Claims

1. A liquid heavy metal reactor aerosol protective coating, characterized by: Including the following settings: The polymer coating is prepared from acrylic monomers, emulsifiers, initiators, and organic solvents; A hydrogel coating is prepared from acrylamide, acrylic acid, a crosslinking agent, a photoinitiator, and a positively charged ionic liquid; The polymer coating and the hydrogel coating are both loaded with nano silver oxide particles.

2. The liquid heavy metal reactor aerosol protective coating according to claim 1, characterized in that: In the polymer coating, the mass ratio of acrylic monomer, emulsifier, initiator and organic solvent is (1-10):(1-5):(10-50).

3. The liquid heavy metal reactor aerosol protective coating according to claim 1, characterized in that: In the hydrogel coating, the mass ratio of acrylamide, acrylic acid, crosslinking agent, photoinitiator and positively charged ionic liquid is (0.5-5):(0.1-1):(0.001-0.01)(0.001-0.01):(0.1-0.5).

4. The liquid heavy metal reactor aerosol protective coating according to claim 1, characterized in that: The acrylic acid-based monomer includes at least three of methyl methacrylate, isobornyl methacrylate, ethyl methacrylate, butyl methacrylate, butyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, and acrylic acid.

5. The liquid heavy metal reactor aerosol protective coating according to claim 1, characterized in that: In the polymer coating, the mass proportion of the nano silver oxide particles is 0.1 wt% to 5 wt%.

6. The liquid heavy metal reactor aerosol protective coating according to claim 1, characterized in that: The positively charged ionic liquid includes at least one of methyltributylphosphine dimethyl phosphate, ethyltributylphosphine tetrafluoroborate, and butyltriphenylphosphine tetrafluoroborate.

7. The liquid heavy metal reactor aerosol protective coating according to claim 1, characterized in that: The hydrogel coating further comprises acid and / or base; the acid and / or base make the pH value of the hydrogel solution be 4-6.

8. A method for preparing the liquid heavy metal reactor aerosol protective coating according to any one of claims 1 to 7, characterized in that: The following steps are involved: The acrylic acid monomer is polymerized in the presence of an emulsifier, an initiator, and an organic solvent, and then nano silver oxide particles are added to prepare a polymer coating precursor solution; Dissolving acrylamide, acrylic acid, a crosslinking agent, a photoinitiator, and a positively charged ionic liquid, and then adding nano silver oxide particles to prepare a hydrogel coating precursor solution; The polymer coating precursor solution is coated to form a film, and then the hydrogel coating precursor solution is coated and photocured to form a film to obtain the liquid heavy metal reactor aerosol protective coating.

9. Use of the liquid heavy metal reactor aerosol protective coating according to any one of claims 1 to 7 in heavy metal aerosol protection.

10. The use according to claim 9, characterized in that: The heavy metal includes at least one of Po, Te, Pb, and Bi.